A lipopeptide biosurfactant from Bacillus sp. Lv13 and their combined effects on biodesulfurization of dibenzothiophene. Issue 68 (19th November 2018) - Lyu, Yinghai; Zhang, Tingting; Dou, Baojuan; Li, Guijiang; Ma, Chengxin; Li, Yangyang
Abstract : Complex interactions among DBT, bacteria and biomolecules play a major role in the absence of lipopeptides. After adding lipopeptides, DBT degrades rapidly to HBP through BDS. Abstract : The process of using biodesulfurization (BDS) to remove sulfur compounds in petroleum has limitations such as low efficiency and low mass transfer. Therefore, it is important to study the combined effects of biosurfactant and the strain on BDS. A thermophilic desulfurization strain, Bacillus sp. Lv13, was isolated from the oilfield and used to produce biosurfactant (BS). The strain was identified as Bacillus licheniformis, a moderate thermophilic bacterium. Its BS was identified as lipopeptide using thin-layer chromatography (TLC), gas chromatography-mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FT-IR). The emulsification efficiency after 24 h ( E 24 ) and critical micelle concentration (CMC) were determined to be 46.93% and 30 mg L −1, respectively. The combined effects of biosurfactant and the strain on BDS was confirmed using the Gibbs assay, GC-MS and BaCl2 test. Results showed that the yield of 2-hydroxybiphenyl (2-HBP) from dibenzothiophene significantly increased after the addition of lipopeptide into the reaction system. This could be illustrated by the stabilization of emulsion, lower CMC value, higher mass transfer rate with the addition of lipopeptide, and the enhancement in the capacity of BDS as well as the catalytic ability of the microbial cell.